Literature Study: Development of Pencak Silat Measurement and Evaluation Test Instruments - Ahmad Bahriyanto; Bambang Budi Raharjo; Setya Rahayu; Fajar Awang Irawan (Universitas Negeri Semarang, 2023)
Instruments as objective measuring instruments in evaluating exercise results. The improvement in the performance of martial arts athletes is always measured by a test instrument. So far from searching on google scholar, there have been many articles published in the development of martial arts instruments. Interpretation of results from literature studies shows mixed results. This literature study aims to find, critically assess, and analyse the results of the development of pencak silat test instruments. The keywords used in the database are the development of pencak silat instruments published within the last 5 years from the period 2019 to 2023. The method used in completing the literature study uses PRISMA guidelines with four stages, namely identification, screening, eligibility, and inclusion and the database is taken from google scholar. Conclusion making is conducted qualitatively. The database is systematically analyzed to search for relevant studies. Articles are filtered independently, and data is obtained through data extraction forms. There are six articles showing the relationship with the development of martial arts test instruments. The main finding of the literature study is the difference in the validity and reliability results of each test instrument developed. This is due to differences in the characteristics of martial arts athletes as subjects in the study. Therefore, it is necessary to reconstruct the research and development of pencak silat test instruments with validity and reliability that can be used in generalization.